Tanggung Jawab Perdata Direksi Perseroan Terbatas Yang Telah Dinyatakan Pailit Terhadap Pajak Terutang (Studi Kasus pada Kantor Wilayah Direktorat Jenderal Pajak Wilayah Bengkulu dan Lampung) - Nuki Nuki (Universitas Lampung, 2021)
Sumber Urip Sejati Utama Ltd. is a company that runs in the fertilizer industry. Technically, Sumber Urip Sejati Utama Ltd.'s board of directors purchase urea fertilizer for the factory, then sold the urea fertilizer to consumers. As a urea fertilizer distributor, Sumber Urip Sejati Utama Ltd. should fulfil tax administration obligations, such as reporting tax payments and calculations. However, Sumber Urip Sejati Ltd.’s administration is highly engineered by the company’s directors because Sumber Urip Sejati Utama Ltd. is operating even though it is declared bankrupt. The situation escalades when the company is faced with unfulfilled tax obligation. Therefore, the main problem in this research is the director board of Sumber Urip Sejati Utama's Ltd. civil liability and legal consequences towards the tax in debt due to the board’s negligence. The research method used in this study is a normative juridical approach, which is an approach based on the primary legal material by examining theories, concepts, legal principles and legislation. The research elaborates that the civil liability of Sumber Urip Sejati Utama Ltd.’s director board towards the tax in debts is in a form of joint responsibility or responsibility. Moreover, the legal consequences faced by the director boards due to their negligence is that directors should bear all of the company's debts to creditors and third parties, to the extent of using the directors' assets to cover the losses.